2010
DOI: 10.5216/cab.v11i3.6800
|View full text |Cite
|
Sign up to set email alerts
|

Frequência De Anticorpos Contra Metapneumovírus Aviário Em Criações Industriais E De Galinhas De Quintal No Pólo Avícola Da Bahia.

Abstract: Este estudo teve como objetivo determinar a frequência de anticorpos contra o metapneumovírus aviário (AMPV) em criações, não vacinadas, de frangos de corte e galinhas de quintal no polo avícola do Estado da Bahia. Coletaram-se 622 amostras de soro de criações de frangos de corte e 268 amostras de galinhas de quintal. A sorologia foi realizada por meio do kit comercial de ELISA indireto. Na análise estatística utilizou-se o teste t de Student com intervalo de confiança de 95%. Detectaram-se aves soropositivas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Studies published in Brazil have reported seroconversion in unvaccinated poultry, proving that the agent is present in industrial farms (Peres et al, 2006) and in free-range poultry (Sales et al, 2010). In any case, this serological profile observed in study 2 indicates the excellent ability of vaccines to produce protection, since the appearance of clinical signs of the disease was not observed at any time during the study.…”
Section: Evaluation Of the Performance Of A New Pentavalent Vaccine I...mentioning
confidence: 57%
“…Studies published in Brazil have reported seroconversion in unvaccinated poultry, proving that the agent is present in industrial farms (Peres et al, 2006) and in free-range poultry (Sales et al, 2010). In any case, this serological profile observed in study 2 indicates the excellent ability of vaccines to produce protection, since the appearance of clinical signs of the disease was not observed at any time during the study.…”
Section: Evaluation Of the Performance Of A New Pentavalent Vaccine I...mentioning
confidence: 57%
“…The high seroprevalence found in this study, 77% of the birds and 89.5% of properties, shows the virus spread in the region and corroborates with other studies. In a study performed in a poultry hearing area in Bahia, Brazil, 77.1% of commercial flocks and 94.12% of backyard flocks surveyed were seropositive for aMPV, Sales et al (2010). We found that the variation coefficient for aMPV within properties ranged from 47.53% to 340%; a high variation coefficient within the same farm could be explained by the diversity of the age of the poultry reared in the same place.…”
Section: Discussionmentioning
confidence: 68%